Urbanaria. - Badurina, Lara; Bernik, Lidija; Bratusa, Mirko; Celestina, Tjasa; Cimolini, Mika; Cosic, Vuk; Drole, Ines; Grzinic, Marina; Herscher, Andrew; Irwin; Jenko, Marija; Kemperle, Bozidar; et al. (Ljubljana : Soros Centre for Contemporary Arts, 1994)
Badurina, Lara ; Bernik, Lidija ; Celestina, Tjasa ; Rozman, Drago ; Bratusa, Mirko ; Cimolini, Mika ; Cosic, Vuk ; Vogrincic, Matej Andraz ; Drole, Ines ; Frlic, Metod ; Vicic, Maja Gspan ; Simoncic, Petra Vari ; Herscher, Andrew ; IRWIN ; Jaksic, Bojan ; Mihorko, Anica ; Prelovsek, Marja ; Pavcic, Tomaz ; Sotlar, Snezana ; Simsic, Miljanka ; Zbontar, Danica ; Jenko, Marija ; Sadar, Almira ; Kamnikar, Gregor ; Kemperle, Bozidar ; Knez, Janez Miso ; Sine, Joze Kos - ; Kovacic, Marko ; Kucina, Matej ; Kugler, Ema ; Kunst, Bojana ; Stromajer, Igor ; Lazetic, Kristina ; Nartnik, Gregor ; Piskar, Primoz ; Somrak, Igor ; Luzar, Majda ; Maechtig, Tomaz ; Vrhunc, Jurij Sadar Ursa ; Core, Mizz Art & Strip ; Ocvirk, Primoz ; Oman, Rok ; Videcnik, Spela ; Peljhan, Marko ; Atol, Projekt ; Pirman, Alenka ; Pivka, Irena ; Pogacar, Tadej ; Potokar, Bostjan ; Potrc, Marjetica ; dom, Produkcija Sokolski ; Prosenc, Natasa ; Pungercar, Marija Mojca ; Rusjan, Rene ; Span, Nika ; Sustersic, Apolonija ; Verzel, Dean ; Vidic, Metod ; Vidrih, Rajko ; VSSD ; Vuga, Darja ; Brener, Aleksander ; Cosic, Vuk ; Vogrincic, Matej Andraz ; Vicic, Maja Gspan ; Simoncic, Petra Vari ; IRWIN ; Kovacic, Marko A. ; Peljhan, Marko ; Pirman, Alenka ; Pogacar, Tadej ; Potrc, Marjetica ; Prosenc, Natasa ; Span, Nika ; Vidic, Metod ; Vidrih, Rajko
2 volumes : part one - part two
biografie
Engels
boek